Descolonizando a cartografia histórica amazônica: representações, fronteiras étnicas e processos de territorialização na Capitania do Pará, Século XVIII - CARDOSO, Alanna Souto (Universidade Federal do Pará, 2019)
The spaces, territories and territorialities of present-day indigenous peoples of Brazil and of Amazonia has been much researched, especially by anthropology, sociology and geography, but little has been invested in a framework of an (ethno)historic cartography that maps the space of the past of these peoples from a plural perspective and with a dialectic that is in dialogue with time, therefore the tridimensional spatial formation, the space conceived (of representations of space), the space perceived (of spatial practices) and the space lived (the space of representations) with respect to the territories and territorialities that were experienced by these peoples in certain phrases of processes of colonial territorialization through which they had passed, and currently, many disintegrated not only through invaded lands, but also dispersed in the memory of contemporary indigenous peoples, especiallymas “emergent” and resistant communities of caboclo riverside peoples of the Lower Tapajós that since the end of the 1990s have reclaimed their indigenous identities, urging the necessity of a “return trip” in the direction of an ethnohistoric cartography of indigenous peoples of the Colonial Amazon through an interdisciplinary and decolonizing methodology of references, documentation, maps, colonial censuses and travel diaries which anchor the current analysis in the first moment to problematize the indigenous representations portrayed in cartography in the era of conquest and in the maps of inhabitants; still debating the ethno-racial question in the labor market through these spatial practices of of Pombaline management envisaged in the colonial censuses; and in the second part of the thesis inward towards lived territory, on the ethnic borders and in the first two phases of processes of territorialization of the colonial Tapajós valley during the 18th century, indeed shining a light on the historical situations that antecede this century, as well as connections with the present time made at the end of that “trip.”